Stress management training: its effects on the anxiety level and performance in the clinical area of third year student nurses - Cada, Marie Esil C. (1996)
This study was conducted to determine the effects of stress Management Training on the anxiety level and clinical performance of third year student nurses. It also wanted to find out the relationship between anxiety level and clinical performance. The study anchored its theoretical foundations on the Transactional Theory of Stress and Adaption (Folkman and Lazarus, 1984) which emphasizes the role of perception in the initiation and reaction to stress.The study utilized the quasi-experimental design with 36 subjects randomly selected and matched according to their A-State A-Trait score and the Palmer Stress Events Inventory Score. The State-Trait Anxiety Inventory (STAI) was utilized to measure the respondent's anxiety level before and after the Stress Management Training. A revised form of the Performance Rating Scale (PRS) was utilized to measure the clinical performance of the respondents. Data gathering lasted for 12 weeks from August 28, 1995 to December 6, 1995.Findings of the study revealed that the study group had a lower mean A-State anxiety score (48.8889) than the control group (50.7778) while in their clinical performance, the study group obtained a higher rating (83.8889) than the control group (82.000). The computed t-test scores for the post A-State (-3.18, p=.005) and clinical performance (3.80, p=.001) were found to be statistically significant at L=.05. On the other hand, there was no significant relationship found between anxiety level and clinical performance in both groups.Based on the findings of the study the following conclusions were drawn: a) Stress Management Training significantly reduced the anxiety level of the study group by 7.76 percent as compared to the control group.b) The study group obtained a higher rating in the clinical area compared to the control group.c) There was a low correlation between anxiety level and clinical performance which was not statistically significant at L=.05. It was recommended that Stress Management Training be incorporated into the nursing curriculum or that Colleges of Nursing should include Stress Management Training into the psychosocial services being offered by the school to their students. Recommendations for further studies were also given.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Stress management; Anxiety -- Testing; Nursing students